Synthesis and characterisation of lipase enzyme immobilised on magnetic nano particles for application in the transesterification of soybean oil to biodiesel - Nui, Pham Xuan; Son, Nguyen Ngoc; Cuc, Le Thi (Petrovietnam Journal, 2013)
In the study, magnetic chitosan microspheres were prepared by the chemical co-precipitation approach using glutaraldehyde as the cross-linking reagent for lipase immobilisation. The lipase enzyme is immobilised on the principle of creating peptides covalently linked via glutaraldehyde as a bridge with chitosan magnetic particles. The catalyst system has been characterised using the following analytical methods: X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared (FT-IR) spectra, and transmission electron microscopy (TEM). The analysis showed that the enzyme was immobilised onto the magnetic nanoparticles. The nanoparticles formed were spherical, uniform in size with average diameters from 12 - 15nm. Using the immobilised lipase, the conversion of soybean oil to fatty acid methyl esters reached 93%wt under the reaction temperature of 40oC and reaction duration of 30h, and methanol/oil amount-of-substance ratio of 4:1 with the three-step addition of methanol.